A Lesson to Unlock Preservice Science Teachers’ Expert Reading Strategies - Mawyer, Kirsten; Johnson, Heather J. (Innovations in Science Teacher Education, 2017)
New standards for K-12 science education task science teacher educators with providing preservice teachers strong preparation that will help them to embrace their role as teachers of science literacy (National Research Council, 2012). Even though there is a growing trend for teacher preparation programs to offer literacy courses that focus on reading in the content areas, often they do not provide aspiring science teachers the science-specific tools needed to teach reading in secondary science contexts. This article addresses the question, “How can we, as science teacher educators, prepare our teacher candidates to teach reading in the context of science?” We designed an initial literacy lesson to help preservice teachers enrolled in two science methods courses to unpack their content knowledge about literacy in science. Our hope was that by unlocking their personal strategies they would be better positioned for engaging in conversations about literacy. We found that using this initial literacy lesson provided our preservice teachers with a solid foundation for engaging in conversations about how to scaffold student reading. This lesson also provided preservice teachers an opportunity to collaboratively develop a common beginner’s repertoire of reading strategies that we subsequently used as a building block for designing activities and lessons that engage middle and high school students in big science ideas and understanding real-world phenomena through reading a variety of kinds of science texts.